Testing the New Parameters affecting The Outcome of Extracorporeal Shockwave Lithotripsy for Upper Ureteric Stones - Mohammed B. Ismail1 , Hasanain F. Hasan Al-Timimi (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Extracorporeal Shock wave lithotripsy (ESWL) is widely used in treating patients with ureteralstones because it is effective, safe, and noninvasive. Based on factors such as size and the location of stones,there is a significant variation in the overall stone-free rate (SFR).Aim of the study: To evaluate the effect of ureteral wall thickness (UWT), stone attenuation, the time fromfirst attack of pain till first session of ESWL and stone/ rib density on the outcome of SWL in the treatmentof upper ureteral stones (UUS).Patient and methods: A prospective study when 127 patients with radio-opaque UUS ranging from 7 to 20mm and treated by ESWL were included in this study. The effect of (stone/ 12th rib) density by KUB, ureteralwall thickness by NCCT and the time from first attack of pain till first ESWL session was studied.Results: The overall successful fragmentation was 75.5%, with the overall success rates in the low density(LD) and high density (HD) groups were 83.8% and 52.94%, respectively. The average number of SWLsessions needed in the two groups for success was 1.9 compared with 2.7 sessions (p<0.05). For stones <10 mm; those with ureteral wall thickness <3.25 mm have success rate about 90.3% VS 69.7% with uretericwall thickness > 3.25 mm which is highly significant. Early ESWL within the first 24 hours of acute attackof first pain has successful fragmentation of 85.45%. With significant effect on number of ESWL sessions.The stone free rate reaches 91.1% for stones <10 mm.Conclusions: The stone free rate is inversely affected by stone /12th rib density ; ureteral wall thickness andthe time from first attack of pain till first session of ESWL, were important predictors of successful ESWL.